Scale development and validation of Transaction Cost Economics typology for contracts: A systems thinking approach. Issue 3 (June 2022) - Cevikparmak, Sedat; Celik, Hasan; Adana, Saban; Uvet, Hasan; Sauser, Brian; Nowicki, David
Abstract: A variety of contract typologies that exist in the literature are helpful in the exploration of different approaches in contractual relations, but only when measured with the right instruments. Although Transaction Cost Economics (TCE) has a distinct, high-level, and abstract typology for contracts, it still lacks a measurement scale. In this paper, a measurement scale for the TCE contract typology (classical, neo-classical, and relational contracts) was developed and validated, using systems thinking approach and experimental design to contribute to the empirical tests of TCE within the contracting realm. First, the antecedents of contract selection within the TCE literature were analyzed using the systemigram technique to visualize and parse out complex relationships that lead to contract selection. The analysis of the TCE Systemigram helped the development of the scale and revealed the need to revisit the risk neutrality assumption embedded in TCE. Second, a measurement scale for the TCE contract typology (classical, neo-classical, and relational contracts) was developed adhering to the original texts of seminal papers and reviews from the TCE literature. Third, the 14-item measurement scale was validated using a series of three vignette-based experimental studies. Key message: This research explores the antecedents of the TCE contract typology and develops a measurement scale for essential characteristics of classical, neo-classical, and relational contracts, as defined in TCE, using systems thinking approach and a novel vignette-based experimental design. Highlights: This research explores the antecedents of the TCE contract typology. A TCE Systemigram was created to visually illustrate the interrelationships of TCE framework. A measurement scale was developed for TCE contract typology. The TCE contract typology measurement scale was validated using a vignette-based experimental design.